(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this scientific article researched the features of the dynamic analysis of hinged-lever hammer mechanisms with a variable reduced moment of inertia, taking into account the reduced gravity forces of the links.